The effect of length of stay in nursing homes on the sleep quality of the elderly - Rian Tasalim; Elsa (Muhammadiyah Journal of Geriatric, 2025)
Background: Sleep disturbances are among the most frequent health problems in older adults, especially those residing in nursing homes. Psychosocial and environmental factors, including length of stay, may affect sleep quality. Prolonged residence in an institution can lead to feelings of loneliness, loss of family connection, and decreased physical activity, all of which contribute to poor sleep. Purpose: This study aimed to analyze the effect of the length of stay at Panti Werda Budi Sejahtera on the sleep quality of elderly residents. The focus was to compare the quality of sleep between residents who had lived for more than five years and those who had lived for five years or less. Methods: This research employed a quantitative correlational design with purposive sampling. A total of 32 elderly respondents, aged 60 years and above, were included according to set inclusion criteria. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data analysis was performed using the Chi-Square test at a 95% confidence level (p < 0.05). Results: 80% of the elderly who had stayed longer than five years reported poor sleep quality, while 63.6% of those with shorter stays reported good sleep quality. Statistical analysis revealed χ² = 4.886 and p = 0.027, indicating a significant relationship between length of stay and sleep quality. Conclusion: Based on the study findings, nursing homes to elderly residents with longer lengths of stay more likely to experience poor sleep quality.